Pd-decorated Si nano-horns as sensitive and selective hydrogen gas sensors. (December 2020) - Lee, Jae-Hyoung; Kim, Jin-Young; Kim, Jae-Hun; Mirzaei, Ali; Kim, Hyoun Woo; Kim, Sang Sub
Graphical abstract: Highlights: Pd-decorated Si nano-horns were successfully synthesized. The optimized gas sensor showed excellent sensitivity and selectivity to hydrogen gas. Catalytic effect of Pd NPs and conversion of Schottky contacts to Ohmic contact enhanced the gas response. Abstract: The semiconductor industry is based mainly on silicon (Si). Therefore, gas sensors based on Si that have high compatibility with semiconductor technology are among the most promising sensing devices. This study examined the effects of the sensing temperature, selectivity, and detection limits for real applications. This paper reports highly selective hydrogen gas sensors fabricated from Pd-decorated Si nano-horns (NHs). First, Si-NHs were prepared using a simple chemical etching method, which was followed by Pd-decoration using a UV irradiation technique. Electrical and gas sensing measurements showed that the resistance of the gas sensors was affected considerably by the sensing temperature as well as the size of the Pd nanoparticles (NPs). Furthermore, the optimized gas sensor could detect as little as 0.1 ppm H2 gas. The present sensors with exceptional performance toward hydrogen gas have potential use as Si-based hydrogen gas sensors.